Questioning the Existence of Artificial Intelligence as a Legal Subject in Indonesian National Law - Itok Dwi Kurniawan; Kristiyadi (UNIVERSITAS PGRI YOGYAKARTA, 2020)
Abstract Discussions related to legal subjects are usually directed at legal subjects of people and legal entities. The development of law in Indonesia has apparently not only presented corporations as new legal subjects, but has now recognized increasingly sophisticated artificial intelligence which will prospectively become new legal subjects. This is a challenge for the government to create qualified regulations related to the use and accountability of legal actions carried out by artificial intelligence. This article was written using a normative legal research method with a conceptual approach, and analyzed deductively. The results of the research contained in this article indicate that regulations related to artificial intelligence should be regulated in separate laws. The existence of artificial intelligence as a legal subject is equated with the position of a legal entity, in the responsibility for artificial intelligence, the identity of artificial intelligence needs to be stated in an authentic deed. Keywords: Artificial Intelligence, Legal Subject, National Law.